A structural synthesis of the Proterozoic Arabian-Nubian Shield in Egypt - Greiling, Reinhard O.; Abdeen, Mamdouh Mahmoud; Dardir, A. A.; Akhal, Hani El-; Ramly, Mahmoud Fawzy el-; El Din Kamal, G. M.; Osman, Ali Farrag; Rashwan, Abdelazeem Ahmed; Rice, Hugh; Sadek, Mohamed F. (Geologische Rundschau, 1994)
Detailed structural geological and related studies were carried out in a number of critical areas in the Proterozoic basement of eastern Egypt to resolve the structural pattern at a regional scale and to assess the general characteristics of tectonic evolution, orogeny and terrane boundaries. Following a brief account of the tectonostratigraphy and timing of the orogenic evolution, the major structural characteristics of the critical areas are presented. Collisional deformation of the terranes ended about 615-600 Ma ago. Subsequent extensional collapse probably occurred within a relatively narrow time span of about 20 Ma (575 - 595 Ma ago) over the Eastern Desert and was followed by a further period of about 50 Ma of late to post-tectonic activity. The regional structures originated mainly during post-collisional events, starting with those related to extensional collapse (molasse basin formation, normal faulting, generation of metamorphic core complexes). Subsequent NNW-SSE shortening is documented by large-scale thrusting (towards the NNW) and folding, distributed over the Eastern Desert, although with variable intensity. Thrusts are overprinted by transpression, which was localized to particular shear zones. Early transpression produced, for example, the Allaqi shear zone and final transpression is documented in the Najd and Wadi Kharit-Wadi Hodein zones. Two terrane boundaries can be defined, the Allaqi and South Hafafit Sutures, which are apparently linked by the high angle sinistral strike-slip Wadi Kharit-Wadi Hodein shear zone with a tectonic transport of about 300 km towards the W/NW. In general, the tectonic evolution shows that extensional collapse is not necessarily the final stage of orogeny, but may be followed by further compressional and transpressional tectonism. The late Pan-African high angle faults were reactivated during Red Sea tectonics both as Riedel shears and normal faults, where they were oriented favourably with respect to the actual stress regime.